Gimme Shelter. Social Distancing and Income Support in Times of Pandemic - Ulugbek Aminjonov; Olivier Bargain; Tanguy Bernard (Institute of Labor Economics (IZA), 2021)
Strict containment limits the spread of pandemics but is difficult to achieve when people must continue to work to avoid poverty. A new role is emerging for income support: by enabling people to effectively stay home, it can produce substantial health externalities. We examine this issue using data on human mobility and poverty rates in 729 subnational regions of Africa, Latin America and Asia during the first year of COVID-19. We focus on within-country differential mobility changes between higher- and lower-poverty regions. Conditional on country-day fixed effects, shelter-in-place orders decrease work-related mobility significantly less in poorer regions. Emergency income support programs seem to help people to reduce their mobility on average, mitigating the poverty-driven gap in mobility between regions and, hence, regional differences in contagion rates.
Keywords: H12; I12; I18; I38; O15; 330; COVID-19; poverty; policy; lockdown; social protection; compliance; mobility